Kerangka Konsep Model Pengembangan Kurikulum Pendidikan Karakter Melalui PAI Berbasis “Tarbiya Mukmin Ulul Albab” - Lailial Muhtifah; Ricka Tesi Muskania (AT-TURATS, 2017)
This paper intends to examine the concept of character education curriculum development through PAI-based tarbiya mukmin ulul albab. the approach used in this research is literature study (library research) with literature review method. The results showed that conceptually the development of the curriculum found a theoretical model with the name "a flower" in accordance with the meaning of education is the process of growing. This conceptual model is an ideal model. The model can also be used as a guide in implementing character education through PAI and as a curriculum diversification. The model has a solid and integrated philosophical foundation from the source of the science of kauliah (Al-Quran and hadith) and the source of kauniah science (empirical/natural phenomena) so that the model is holistic and flexible.